Do Survey Data Help Identify Supply and Demand Shocks in Sign-restricted SVARs? - Leonard Salzmann (ZBW - Leibniz Information Centre for Economics, 2024)
Sign-restricted SVARs are typically characterized by high identification uncertainty. However, using external proxies can be helpful in this context. In this paper, I use business survey data to inform an SVAR of aggregate supply, demand and monetary policy shocks for the euro area. In the surveys, companies report input factors that limit their business activities. I show that sign-identified model sets are very heterogenous and produce shocks that are only weakly related to survey-based input shortage indicators. In contrast, combining sign restrictions with information from these shortage indicators narrows the set of admissible impulse response functions and affects policy-related conclusions drawn from the model.
Keywords: 330; Proxy VARs; SVAR; sign restrictions